2001
DOI: 10.1007/pl00009997
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the ability to form ectomycorrhizas in the F1 progeny of an interspecific poplar (Populus spp.) cross

Abstract: The aim of this study was to determine the existence of a genetic basis for the ability to form ectomycorrhiza on a model angiosperm tree (Populus, poplar). Parental clones and 18 progeny from a controlled interspecific cross between Populus deltoides and Populus trichocarpa were grown in a glasshouse and inoculated with mycelium of the ectomycorrhizal fungus Laccaria bicolor. Three months after inoculation, the percentage of mycorrhizal root tips was determined for each inoculated plant. The data indicate var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 14 publications
10
42
0
Order By: Relevance
“…Our findings and that of Gehring et al [8], Khasa et al [10], Tagu et al [11,12], van der Heijden and Kuyper [13] and Walker and McNabb [14] imply that both factors, former land use and clone type, are important determinants of mycorrhizal colonization. The land use types represented, beside the abiotic factors, the different inoculum capacities and were therefore the most important factors determining the mycorrhizal abundance and diversity on the roots of poplars.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our findings and that of Gehring et al [8], Khasa et al [10], Tagu et al [11,12], van der Heijden and Kuyper [13] and Walker and McNabb [14] imply that both factors, former land use and clone type, are important determinants of mycorrhizal colonization. The land use types represented, beside the abiotic factors, the different inoculum capacities and were therefore the most important factors determining the mycorrhizal abundance and diversity on the roots of poplars.…”
Section: Discussionsupporting
confidence: 72%
“…During the early stage of growth, the main colonizers of poplar roots are AM fungi, which are subsequently replaced by ECM fungi [15]. The ratio between ECM and AM colonization of poplars is showing a broad range and has been found to be influenced by environmental factors and host genetics [10][11][12][13][14]. Plant genotypes have been shown to differ in both their ability to form mycorrhiza, and in the relative benefit received from this mycorrhizal colonization [9,30].…”
Section: Richness and Diversity Of Mycorrhizamentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that signifi cant advances in understanding these highly specifi c interaction can be made by focusing on the types of polymorphisms that occur at the species level. Tagu et al ( 2001 ) reported signifi cant segregation in Populus colonization by the symbiont Laccaria bicolor in F 1 progeny from a P. trichocarpa x P. deltoides interspecifi c cross. Further, Labbé et al ( 2011 ) suggested preferential colonization of P. trichocarpa compared to P. deltoides and mapped QTL associated with percent colonization in the F 1 pedigree family 54B.…”
Section: Indels Based On Resequenced Genotypesmentioning
confidence: 97%
“…The ability of poplar trees to form ectomycorrhizas is under genetic control (Tagu et al 2001). Heritability of the ectomycorrhizal trait was investigated in Pinus elliottii (Rosado et al 1994) and a strong narrow-sense heritability was found (0.81) for the percentage of ectomycorrhizas formed.…”
Section: Plant Responses Upon Symbiosis Developmentmentioning
confidence: 99%